A short typology of ethnographic genres: or ways to write about other peoples - Gatewood, John B. (1984)
All descriptions are based on certain criteria, explicit but often implicit. In ethnography, the criteria include what natives do and think, the values of the ethnographer, the concerns of the intended audience, and the subtle constraints of the currently preferred literary style for writing about other peoples. This essay focuses on these stylistic constraints and identifies several genres of ethnographic writing. By recognizing and then expanding the hidden literary dimension in our ethnographies, we may hope to achieve a more complete rendering of the human condition.